Pengaruh Investment Opportunity Set dan Profitabilitas terhadap Kebijakan Dividend - Winda Astri HIdayat; R Deni Muhammad Danial; Dicky Jhoansyah (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study is to determine the effect of investment opportunity set (IOS) and profitability on dividend policy in insurance companies listed on the Indonesia Stock Exchange. The use of the method uses purposive sampling. The analysis technique used is simple linear analysis, multiple linear analysis, and hypothesis testing is a partial statistical test (t test) and simultaneous test (f test). The results of the t test show that the investment opportunity set (IOS (X1) influences positive but not significant to dividend policy, Profitability (X2) has a negative and not significant effect on dividend policy.Based on the F value test together the investment opportunity set and profitability do not have a significant effect on dividend policy (Y) Based on the test the coefficient of determination is 0.361 It can be interpreted that the effect of Investment Opportunity Set (IOS) and Profitability on dividend policy is 13.03%, while the remaining 86.97% is influenced by other factors not explained in this study. Keywords : Investment Opportunity Set, Profitability, Dividend Payout Ratio